2005
DOI: 10.1109/tbme.2004.842790
|View full text |Cite
|
Sign up to set email alerts
|

Localized Electrical Nerve Blocking

Abstract: Localized electrical nerve blocking was investigated in computer simulation and in vivo trials for sinusoidal frequencies between 5 and 20 kHz. Computer simulations indicated that a localized transmission block of the axons could occur in each of the axon models. An approximation of nerve stimulation was derived from individual axon simulations conducted over axon diameters of 5-15 microm and electrode to axon distances of 0.25 to 2.0 mm. Examination of the membrane voltage and ionic gate potentials indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
146
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(155 citation statements)
references
References 13 publications
6
146
1
Order By: Relevance
“…11). However, previous studies using animals (Bhadra et al, 2006;Bhadra and Kilgore, 2005;Bowman and McNeal, 1986;Kilgore and Bhadra, 2004;Rehoul and Rosenblueth, 1939;Rosenblueth and Rehoul, 1939;Tai et al, 2004;2005c;Tanner, 1962;Williamson and Andrews, 2005) showed that the minimal blocking frequency varied between 1 kHz and 10 kHz in different nerves of various species using different electrode geometries. Therefore, the temperature might be one of the factors that could influence the minimal blocking frequency.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…11). However, previous studies using animals (Bhadra et al, 2006;Bhadra and Kilgore, 2005;Bowman and McNeal, 1986;Kilgore and Bhadra, 2004;Rehoul and Rosenblueth, 1939;Rosenblueth and Rehoul, 1939;Tai et al, 2004;2005c;Tanner, 1962;Williamson and Andrews, 2005) showed that the minimal blocking frequency varied between 1 kHz and 10 kHz in different nerves of various species using different electrode geometries. Therefore, the temperature might be one of the factors that could influence the minimal blocking frequency.…”
Section: Discussionmentioning
confidence: 95%
“…The block of spontaneous neuronal activity was always coincident with a stimulus-induced rise in extracelluar potassium concentration, suggesting that a constant potassium outflow from the neurons was induced by the stimulation. The stimulation frequency to block the hippocampal neuron is relatively low (<500 Hz) compared to the minimal stimulation frequency required to block the axonal conduction (1-10 kHz) (Bhadra et al, 2006;Bhadra and Kilgore, 2005;Bowman and McNeal, 1986;Kilgore and Bhadra, 2004;Rehoul and Rosenblueth, 1939;Rosenblueth and Rehoul, 1939;Tai et al, 2004;2005c;Tanner, 1962;Williamson and Andrews, 2005). However, this frequency discrepancy might be caused by the slow membrane dynamics of the neuron and the longer duration action potential.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations